Pediatric Hodgkin’s lymphoma: experience from a tertiary cancer center in North East India - Munlima Hazarika; Cliffton Sutnga; D., Nithin Raj; Partha S. Roy; Satya S. Sarangi; Raghavender Reddy; Sreya Mallik; Anupam Sharma (International Journal of Contemporary Pediatrics, 2023)
Background: Hodgkin’s lymphoma is a clonal malignant lymphoid proliferation, which originates from the germinal centers of B cells. This study was conducted to observe the socio-epidemiological profile of Hodgkin’s lymphoma in a tertiary cancer care centre from North East India. Methods: All patients from 0 to 18 years of age group with histopathologically proven diagnosis of HL, presenting to department of medical & pediatric oncology at Dr. Bhubaneswar Borooah cancer Institute during the period January 2012 to December 2019 were included in the study. Clinical parameters assessed included age, sex, locality, occupation, presenting symptoms, performance status, site of lymph node involvement, treatment modality, response to treatment, progression free survival and overall survival. Results: A total of 64 patients with histopathologically confirmed diagnosis of HL were registered in lymphoma joint clinic of BBCI from January 2012 to December 2019. The mean age was 12.68±4.71 years. Out of 64 patients, 54 (84.4%) belonged to rural areas and 10 patients (15.6%) to urban areas. Complete response was observed in 93.5% patient with limited risk disease, 73.24% with intermediate risk and 60% with advance stage. The overall survival and event free survival rates of 91% and 78.1%, respectively, were observed at 4 years. Conclusions: This study provides insight to incidence, demographic profile, overall response rates and survival pattern with other secondary objectives such as complete response rate, compliance rate and toxicity assessment among children with Hodgkin lymphoma belonging to Northeastern India.